Alternative fixation system for implant-retained overdenture: case report - Mariana Lima da Costa VALENTE; Denise Tornavoi de CASTRO; Frank Lucarini BUENO; Ana Beatriz Vilela TEIXEIRA; Geyson Galo da SILVA; Andréa Cândido dos REIS (Faculdade São Leopoldo Mandic, 2019)
The aim of this case report was to describe a prosthetic rehabilitation associated with an alternative model of polymer capsule for fixation system of implant-retained overdentures. Patient sought treatment at the clinic of School of Dentistry of Ribeirão Preto, due to lack of retention of their conventional total superior prostheses and inferior overdenture. The initial complaint was clinicallyconfirmed by altered intermaxillary relationships and severe reabsorption of the maxillary crest. In order to restore the function and improve its quality of life, it was proposed a prosthetic solution including implant fixed prosthesis to maxilla and a mandibular overdenture, with ball-type attachments associated with an alternative model of polymer capsule. This treatment was proposed inorder to reestablish the intermaxillary relationships and adequate occlusion, maintain retention and stability of the prosthesis. At the end of treatment and during a one-year follow-up of the case, the patient reported satisfaction and significant improvement in quality of life.